Relatıonshıps Between Aırway Adequacy And Vertıcal Cranıofacıal Confıguratıon - M. Murat Özbek; Dilek Erdem (Galenos Yayinevi, 1993)
This study was carried out on the natural head posture cephalograms of 99 subjects (45 males and 54 females), in the age range of 19-29 years, and aimed at searching for the associations between airway adequacy and vertical craniofacial configuration. Beside the conventional measurements, variables based on the natural head position and extracranial true HOR and VER reference lines were used for the evaluation of the vertical pattern. Although not as frequent as expected, statistically significant correlations were observed between the variables indicating airway adequacy and facial morphology, which might suggest the facts that a decrease In the airway capacity results with the posterior rotation of the mandible and with an increase in the anterior facial height.